1991
DOI: 10.2105/ajph.81.4.501
|View full text |Cite
|
Sign up to set email alerts
|

Black-white differences in cancer prevention knowledge and behavior.

Abstract: Data from the 1987 National Health Interview Survey Cancer Control Supplement were used to estimate multivariate logistic regression models of diet change, mammography utilization, stool blood test utilization, and smoking. Predictor variables included race, sex, age, income, dietary concerns, and four knowledge-related variables: education and three measures of cancer prevention knowledge. When knowledge variables were included in the models, race was not a significant predictor of behavior, with one exceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(48 citation statements)
references
References 6 publications
5
43
0
Order By: Relevance
“…Several researchers have reported on the relationship between knowledge and risk-reduction behavior. Moro et al 41 reported a positive association between knowledge of Chikungunya disease and future intentions to use mosquito repellent in Italy following the first reported outbreak of the disease in the northern hemisphere. Jepson et al 42 reported that knowledge of cancer risk factors was a significant explanatory variable in the observed differences in cancer-preventive behavior between black and white racial groups in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have reported on the relationship between knowledge and risk-reduction behavior. Moro et al 41 reported a positive association between knowledge of Chikungunya disease and future intentions to use mosquito repellent in Italy following the first reported outbreak of the disease in the northern hemisphere. Jepson et al 42 reported that knowledge of cancer risk factors was a significant explanatory variable in the observed differences in cancer-preventive behavior between black and white racial groups in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…15 Another explanation is that minorities may not perceive the value of obtaining early and preventive health care, thus diminishing their use of outpatient services. [42][43][44] However, as above, minorities with equal access to primary care receive equal or greater preventive services, and multiple programs directed at increasing specific preventive care interventions have succeeded in diminishing or eliminating the gap between minorities and nonminorities, particularly in the areas of breast and cervical cancer screening. 45,46 Despite lower receipt of care in the outpatient setting, it does not appear that minorities turn to emergency rooms for care disproportionately.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive factors such as knowledge and beliefs about the outcomes associated with CRC screening and the desirability or undesirability of those outcomes (i.e., attitudes toward screening), and perceptions about one's ability (or self efficacy) to engage in screening, will influence CRC screening adherence by shaping motivation to be screened. These cognitive factors have been shown to vary by race [35][36][37][38][39][40][41] and hence, may contribute to racial differences in CRCS. The framework assumes that medical and social environmental factors can affect adherence by determining whether an individual has access to screening (i.e., is offered a screening procedure and resources for conducting the procedure are locally available) or by influencing the accessibility of screening (by determining the availability of things such as transportation to and from a colonoscopy appointment).…”
Section: Conceptual Frameworkmentioning
confidence: 99%